Winter inverse lake stratification under historic and future climate change. Issue 4 (9th December 2021) - Woolway, R. Iestyn; Denfeld, Blaize; Tan, Zeli; Jansen, Joachim; Weyhenmeyer, Gesa A.; La Fuente, Sofia
Abstract: Millions of lakes inversely stratify during winter. Seemingly subtle variations in the duration of winter stratification can have major ecological effects by, for example, altering the vertical distribution of oxygen and nutrients in lakes. Yet, the influence of climate change on winter stratification has been largely unexplored. To fill this knowledge gap, here we used a lake‐climate model ensemble to investigate changes in winter stratification from 1901 to 2099 across 12, 242 representative lakes situated throughout the Northern Hemisphere. By the end of the 21 st century, winter stratification duration is projected to shorten by an average of 18.5–53.9 d under Representative Concentration Pathways (RCPs) 2.6–8.5. Projected changes are faster in warmer geographical regions, in which 35–69% of lakes will no longer inversely stratify by 2070–2099 under RCPs 2.6–8.5. This shortening and loss of winter stratification will likely have numerous implications for lakes, including the misalignment of lifecycle events causing shifts in biodiversity.